PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN DANA BAGI HASIL TERHADAP BELANJA MODAL - Like Refelika Dewi, - (2019)
The purpose of this study is to examine the effect of Local Revenue, General Allocation Funds, Special Allocation Funds, adn Profit Sharing Funds to The Capital Expenditure to all Regencies/Cities in the Province of Central Java, during 2015-2017 time period. In this study , the sample is consisted of 35 Regencies/Cities that was analysed using purposive sampling method, with 93 total amount of sample. The data that used is a secondary data. This secondary data analysis was conducted using data collected from Local Government Finance Report or specifically in Central Government budget outcomes section, published by Audit Board of The Republic of Indonesia (BPK RI). Hypothesis testing in this study was using multiple regression method and analysed by SPSS 24 software and significance lever of 5% (0,05). The result partially showed that Local Revenue variable does not significantly impact Capital Expenditure, on the other hand General Allocation Funds, Special Allocation Funds, and Profit Sharing Funds significantly impacted the Capital Expenditure.